Use of the prognostic nutrition index as a predictive biomarker in small-cell lung cancer patients undergoing immune checkpoint inhibitor treatment in the Chinese alpine region - Wu, Yunjiao; Yang, Jing; Qiao, Xinyi; Li, Yingjie; Zhao, Rui; Lin, Tie; Li, Xiaoli; Wang, Meng (Frontiers in Oncology, 2023)
Whether the prognostic nutritional index (PNI), which is suggested to reflect systemic inflammation and nutritional status of patients, could be used as an effective prognostic factor for small-cell lung cancer (SCLC) has not yet been clarified. The purpose of this study was to verify the prognostic value of the PNI in SCLC patients treated with programmed cell death ligand-1/programmed cell death 1 (PD-L1/PD-1) inhibitors in the alpine region of China. We analyzed PNI status in a cohort of 110 SCLC patients treated with PD-L1/PD-1 inhibitors between March 2017 and May 2020. Blood samples were obtained prior to PD-L1/PD-1 inhibitor treatment and analyzed. To evaluate the prognostic value of the PNI, univariable and multivariable analyses of progression-free survival (PFS) and overall survival (OS) were performed. Results indicated that an elevated PNI was associated with significantly lower risk of death [mPFS: 12.5 vs. 8.0 months, hazard ratio (HR) = 0.33, p < 0.001 and mOS: 17.5 vs. 12.6 months, HR = 0.37, p = 0.008, respectively]. In the multivariate analysis, low PNI was significantly associated with worse PFS and OS (p < 0.001, p = 0.001). Additionally, Pearson correlation analysis between PNI and disease control rate (DCR) showed that PNI status was positively correlated with DCR (p < 0.001, r = 0.349). Therefore, the PNI may be a promising biomarker of treatment efficacy and prognosis in SCLC patients treated with PD-L1/PD-1 inhibitors in the alpine region of China.